Attention Allocation for Dysphoric Information in Adults with Depression Symptoms Using Eye-tracking and Mouse-tracking - Mary E. McNamara; Jason Shumake; Christopher G. Beevers (PLoS ONE, 2025)
Biased attention for dysphoric stimuli is thought to maintain depression, but poor measurement has limited prior tests of this hypothesis. The current study examined the association between biased attention for dysphoric information and depression using a novel free viewing attention bias task combined with measuring line of visual gaze via eye tracking or a behavioral proxy for line of visual gaze via mouse tracking in three samples of college students using in-person eye-tracking (Experiment 1, N =  129) and remotely collected mouse-tracking (Experiment 2, N =  79; Experiment 3, N =  154). Mixed effects regression analyses revealed that depression severity was significantly associated with greater attention for dysphoric stimuli in Experiments 1 and 2, but not Experiment 3. Results suggest that depression severity is associated with attention for dysphoric information (although findings from Experiment 3 temper this conclusion) and that eye- and mouse-tracking may be good options for measuring attention bias in depression. Additional work using longitudinal research designs seems warranted to further examine the relationship between attention bias for dysphoric information and the maintenance of depression.